External capital investment flows in Costa Rica between 1980 and 2016 - Ugalde Hernández, Oscar (2018)
Through econometric testing of the determinants of the external capital flows inflows towards Costa Rica in the period 1980-2016, it is determined that Gross National Savings and Commercial Openness are key influencing elements in the attraction of foreign direct investment. Therefore, the impact of these variables along other relevant ones such as the rate of population growth, inflation, the financial sector activity through its stock market, could have an effect on per capita income through the attraction of external capital flows. A robust econometric model is built and a series of various models are tested, and the conclusions reached are consistent in all of them. Thus the recommendations proposed are geared towards public policy with a greater emphasis on promoting national savings and towards a greater commercial openness.